STRATEGI DINAS SOSIAL DALAM UPAYA PEMBERDAYAAN BAGI PENYANDANG DISABILITAS KABUPATEN BULELENG - Suryadiningrat, I Kadek G Lanang; Supriliyani, Ni Wayan; Yasintha, Putu Nomy (CITIZEN CHARTER, 2023)
The main focus of this research is the Strategy of the Social Service in Empowering Persons with Disabilities in Buleleng Regency. This study aims to explain how the Strategy of the Social Service in Empowering Persons with Disabilities in Buleleng Regency. This strategy is analyzed using John Bryson's strategic planning process and using SWOT analysis. This study uses a qualitative approach because this study describes how the Social Service Strategy in Efforts to Fulfill Accessibility Rights for Persons with Disabilities. The results of this study indicate that women's participation has not fully occurred as expected in an effort to empower people with disabilities in Buleleng Regency, the Buleleng Regency Social Service provides social assistance to Persons with Disabilities. The formal mandate carried out by the Buleleng Regency Social Service regarding the Empowerment of Persons with Disabilities is in the form of the Buleleng Regency Regional Regulation Number 2 of 2019 concerning the Protection and Fulfillment of the Rights of Persons with Disabilities. The Social Service of Buleleng Regency has carried out the mandated mission to carry out empowerment activities for people with disabilities. However, the Social Service of Buleleng Regency needs to pay attention to threats in the form of human resources who are difficult to move forward, and the lack of socialization so that they cannot reach all areas in Buleleng Regency. Evidence of the performance of the Social Service Office of Buleleng Regency in implementing the Empowerment of Persons with Disabilities program is that it has carried out mentoring and training for Potential Persons with Disabilities, in order to improve the economic level of Persons with Disabilities. The Social Service of Buleleng Regency assumes that it has achieved its development vision. Keywords: Strategy, Empowerment, Persons with Disabilities